2010
DOI: 10.1108/09513551011032473
|View full text |Cite
|
Sign up to set email alerts
|

E‐governance for improved public sector service delivery in India, Ethiopia and Fiji

Abstract: PurposeThe purpose of this paper is to explore the extent of corruption in India, Fiji and Ethiopia and survey citizen perception of how e‐governance could fight corruption. The main objective is to investigate and explore the potential of e‐governance applications in three countries representing three different regions of Asia, Africa, and Oceania.Design/methodology/approachA survey was conducted over 918 citizens in India, Ethiopia and Fiji using convenience random sampling. A structured questionnaire was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 24 publications
(30 reference statements)
2
49
0
2
Order By: Relevance
“…Like much of the other literature reviewed, however, Moraa and her colleagues did not provide evidence that these technologies were having an impact on service delivery. E-governance (using ICTs to improve governance outcomes), e-government (increasing efficiency of government services through creation of publicly accessible online platforms), and mobile governance (m-governance) were also major themes in the literature (Atnafu et al 2011;Crandall and Mutuku 2011;Minishi-Majanja and Ondari-Okemwa 2009;Mitullah and Waema 2011;Mutula 2008;Pathak et al 2007;Pathak et al 2012;Rorissa and Demissie 2010;Singh et al 2010;Thomas et al 2010;Waema 2011;Yonazi et al 2012). Many of the pieces in this category, however, focused on measuring the e-readiness of towns and/or countries rather than evaluating the results of e-governance initiatives.…”
Section: Icts and Statebuildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Like much of the other literature reviewed, however, Moraa and her colleagues did not provide evidence that these technologies were having an impact on service delivery. E-governance (using ICTs to improve governance outcomes), e-government (increasing efficiency of government services through creation of publicly accessible online platforms), and mobile governance (m-governance) were also major themes in the literature (Atnafu et al 2011;Crandall and Mutuku 2011;Minishi-Majanja and Ondari-Okemwa 2009;Mitullah and Waema 2011;Mutula 2008;Pathak et al 2007;Pathak et al 2012;Rorissa and Demissie 2010;Singh et al 2010;Thomas et al 2010;Waema 2011;Yonazi et al 2012). Many of the pieces in this category, however, focused on measuring the e-readiness of towns and/or countries rather than evaluating the results of e-governance initiatives.…”
Section: Icts and Statebuildingmentioning
confidence: 99%
“…A handful of the e-governance studies (Atnafu et al, 2011;Crandall and Mutuku 2011;Mitulla and Waema 2011;Ochara 2012;Pathak et al 2007Pathak et al , 2012Singh et al 2010;Thomas et al 2010;Waema 2011;Yonazi et al 2012) attempted to assess the impact of e-government projects through interviews with citizens about how they themselves assess these initiatives. Crandall and Mutuku (2011) noted that health, education, and immigration services are among the top sectors employing e-services in Kenya, but found that most of the individuals surveyed believed face-to-face interaction with government is most effective.…”
Section: Icts and Statebuildingmentioning
confidence: 99%
“…As noted by Singh et al, (2010), e-government "…entails streamlining operational processes, transcribing information held by government agencies into electronic form, linking disparate databases, and improving ease of access to services for members of the public" (p. 256). E-government has also been promoted as a strategy of public sector reform, with a focus on how it can improve the managerial process (Kudo, 2010).…”
Section: Ict Enabled E-governmentmentioning
confidence: 99%
“…Similarly, in reviewing the literature to identify the potential role of egovernment in reducing corruption, Singh et al, (2010) emphasize that egovernment eliminates discretion from the equation by removing intermediary services and allowing citizens to conduct transactions themselves. Andersen and Rand (2006) also study the relation between corruption and e-government and examine a cross-section of countries from the 1997 to 2002 period.…”
Section: Ict Enabled E-governmentmentioning
confidence: 99%
See 1 more Smart Citation